2014
DOI: 10.1039/c4nr04453c
|View full text |Cite
|
Sign up to set email alerts
|

Strategy and mechanism for controlling the direction of defect evolution in graphene: preparation of high quality defect healed and hierarchically porous graphene

Abstract: In this paper, a novel approach for controlling the direction of defect evolution in graphene through intercalation of organic small molecules into graphite oxide (GO) combined with a one-pot microwave-assisted reaction is reported. By using ethanol as intercalator, the bulk production of high quality graphene with its defects being satisfactorily healed is achieved. The repair of defects using extraneous carbon atoms and the hybrid state of these carbon atoms are definitely demonstrated using isotopic tracing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…Table 2). As will be further discussed below in the light of the electrochemical characterization results, a potential consequence of the extensive removal of oxygen atoms is that the remaining aromatic domains could incorporate significant amounts of unsaturated, highly reactive edges [31,32], particularly when activation is carried out at a lower temperature that is less carboxylic and ester functionalities). Generally, the C 1s XPS spectrum of a pure graphitic material without heteroatoms presents an asymmetric shape.…”
Section: Morphology Structure Texture and Surface Chemistry Of The mentioning
confidence: 99%
“…Table 2). As will be further discussed below in the light of the electrochemical characterization results, a potential consequence of the extensive removal of oxygen atoms is that the remaining aromatic domains could incorporate significant amounts of unsaturated, highly reactive edges [31,32], particularly when activation is carried out at a lower temperature that is less carboxylic and ester functionalities). Generally, the C 1s XPS spectrum of a pure graphitic material without heteroatoms presents an asymmetric shape.…”
Section: Morphology Structure Texture and Surface Chemistry Of The mentioning
confidence: 99%
“…As shown in Figure 1C, GO exhibited an initial weight-loss below 200 °C due to the desorption of interlamellar water. 43 The main weight loss then occurred within 200−500 °C, which is attributed to the decomposition of the oxygen-containing groups. As a temperature higher than 500 °C, the further weight loss is due to the decomposition of the more stable functional groups.…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that a carbon rich atmosphere might repair the defects of carbon based materials and improve their electrical conductivity. 35,36 The active sample GCA/C was prepared and the electrochemical performances of GCA, GCA/C and GCA/CNT were characterized by CV test to understand the electrochemical behaviour changes of GCA/CNT. It is observed that all the three electrodes exhibit quasi-rectangular curves at low scan rates of 5 mV s À1 (Fig.…”
Section: Electrochemical Performancementioning
confidence: 99%
“…Moreover, the added carbon nanotubes may increase the electrical conductivity and improve the electrochemical performance by forming a unique three dimensional electrical conductive network. In addition to carbon nanotubes, the added carbon source at high temperatures may heal the defects of the pyrolyzed resol carbon and graphene sheets, 35,36 which further enhance the electrochemical performance of GCA/CNT.…”
Section: Introductionmentioning
confidence: 99%